The symptoms at the center: Examining the comorbidity of posttraumatic stress disorder, generalized anxiety disorder, and depression with network analysis. (February 2019) - Price, Matthew; Legrand, Alison C.; Brier, Zoe M.F.; Hébert-Dufresne, Laurent
Abstract: Comorbid mental health disorders are highly common in trauma-exposed individuals with posttraumatic stress disorder (PTSD), depression, and generalized anxiety disorder (GAD) among the most common co-occurring conditions. Network models of psychopathology offer a novel method to understand how this comorbidity manifests. The present study examined the presence of symptom communities (groups of highly connected symptoms) within a network of these disorders and hub symptoms (symptoms that connect such communities). Cross-sectional data were obtained from a community sample (N = 1184) of trauma exposed adults. Network analyses identified 5 communities: 1 containing all depression and GAD symptoms and 4 for PTSD. The PTSD communities corresponded to symptoms of intrusion and avoidance, hyperarousal, dysphoria, and negative affect. These communities had varying levels of connectivity to the Depression & GAD community. Symptoms of GAD (inability to relax) and PTSD (restricted or diminished positive emotion) were identified as key hub symptoms for the network. The results suggest symptoms of depression and GAD are highly interrelated and that PTSD is heterogeneous. The comorbidity among these diagnoses is thought to stem from their overlap with negative affect. Highlights: Symptoms of GAD and MDD were more densely connected to each other than to PTSD. 5 communities were detected. MDD and GAD symptoms formed a single community. PTSD was divided into 4 communities that did not correspond to the DSM 5 clusters. Inability to relax and restricted affect were hub symptoms. Comorbidity likely occurs via indirect relations established by the hub symptoms.